Pengaruh Jenis Hidrokoloid Terhadap Karakteristik Fisik Dan Sensoris Roti Tawar Bebas Gluten - Utami, Komang Triani; Suparthana, I Putu; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 1 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i01.p06, 2024)
Fresh bread is generally made from wheat flour but it cannot be consumed by people with coeliac or those with gluten sensitivity. Rice flour can be used as a substitute for wheat flour because it has physico-chemical characteristics in the form of amylose and amylopectin which are similar to wheat, as well as the role of rice and its processed foods in the consumption of Asian society, especially Indonesia. This study aims to determine the effect of hydrocolloid addition on the physical and sensory quality of gluten-free white bread and to determine the type of hydrocolloid that has the best effect on the physical and sensory quality of gluten-free white bread. The experiment used a completely randomized design with the treatment of hydrocolloid types consisting of 6 levels (Xanthan Gum, Konjac, Pectin, Carboxymethyl Celulose, Hydroxypropyl Methyl Celulose, and Psyllium Husk). Each treatment was repeated three times resulting in a total of 21 experimental units. Parameters observed were moisture content, hardness, volume development, and sensory tests on pore uniformity, texture, mouthfeel, and overall acceptance using a hedonic scale. Data were analyzed using Analysis of Variance and on treatments that showed a significant effect is then continued with DMRT (Duncan Multiple Range Test) test. The results showed that the addition of various hydrocolloids significantly affected the physical characteristics of fresh bread compared to those without hydrocolloids. Among the hydrocolloids tested, the addition of xanthan gum showed the best results in physical and sensory characteristics, namely with a moisture content value of 39.25 percent, a volume development value of 24.5 percent, with a sensory assessment of pore uniformity, texture, value, mouthfeel and overall acceptance rather like. However, xanthan gum has a texture analysis value of 12.58N. It can be concluded that the addition of hydrocolloids affects the physical characteristics (moisture content, hardness, and development volume) and sensory (pore uniformity, texture, mouthfeel, and overall acceptance) of gluten-free white bread for the better. Keywords: Gluten Free Bread, Hydrocolloids, Physical Characteristics, Sensory Characteristics.